2019
DOI: 10.5004/dwt.2019.24247
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium isotherm and kinetic study of the adsorption of organic pollutants of leachate by using micro peat-activated carbon composite media

Abstract: The suitability of micro peat (MP) and activated carbon (AC) mixed media as a composite adsorbent for the landfill leachate treatment in terms of COD reduction and color removal was investigated in this study. All the adsorption media was pulverized and sieved to a particle size of 150 μm. The MP-AC composite media efficiently removed 87% COD at optimal ratio 1.5:2.5 and 74% color at optimal ratio 2.0:2.0, within 120 min of contact time, 200 rpm of shaking speed at pH 7. The findings revealed that Langmuir iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…achieved a high level of removal of Fe and colour from a LL using a commercial AC and a low‐cost natural adsorbent obtained from peat at pH 7. This adsorbent material showed kinetic data that fitted adequately with a pseudo‐second‐order model, and considering the adsorption energy, the author also observed that chemisorption is the limiting controlling step for colour and COD reduction …”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…achieved a high level of removal of Fe and colour from a LL using a commercial AC and a low‐cost natural adsorbent obtained from peat at pH 7. This adsorbent material showed kinetic data that fitted adequately with a pseudo‐second‐order model, and considering the adsorption energy, the author also observed that chemisorption is the limiting controlling step for colour and COD reduction …”
Section: Resultsmentioning
confidence: 81%
“…This adsorbent material showed kinetic data that fitted adequately with a pseudo-second-order model, and considering the adsorption energy, the author also observed that chemisorption is the limiting controlling step for colour and COD reduction. 45 The best results were obtained after a longer adsorption period, which allowed more time for the mass transfer. 46 The increase in pollutant adsorption was enhanced by longer contact time due to the decrease in the boundary layer resistance of the adsorption layer.…”
Section: Toxicity Analysismentioning
confidence: 99%
“…Therefore, the percentage removal was frequently used to determine the performance of macrocomposite which assesses how many contaminants were removed. Performance of COD and SS percentage removal based on fixed-bed adsorption column regarding the flow volume can be evaluated through the equation (3) [10]:…”
Section: Percentage Removalmentioning
confidence: 99%
“…In contrast, adsorption processes have the advantage of being able to remove a wide range of substances, easy to use, and with no toxic by-product generation (Dąbrowski, 2001). In comparison to other technologies, adsorption is suitable for the removal of organics due to large surface area and competitive sites for attachment of organics on the surface of the adsorbent (Rosli et al, 2019). However, the operational cost of adsorption for leachate treatment is still high and the adsorption of MPs may be limited by competition with and fouling by the co-existing bulk organics (Guillossou et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%